(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research aims to clarify the advantages of using the regression method as analytical procedure in the tax audit to reducing the examination cost , time, effort, human and material resources, and represents an applied study in the General Commission of taxes. In order to achieve its objectives the research has used in the theoretical side the descriptive approach (analytical), and in the practical side regression method has been applied to the research sample represented by the soft drinks company that is subject to the tax settlement for the year 2014, where the value of sales has been verified by using the regression method without conductinga comprehensive examination. The most important results of the research indicate that the regression analysis works to determine the reasonableness of the numbers in the financial statements for one variable of their variables based on an independent variable that leads to facilitate the decision-making process without the need for a comprehensive examination of these elements and by depending on the historical information for this variable. The regression analysis saves time, effort and cost to determining the validity of a particular variable such as sales without the need for a comprehensive examination which may take considerable time, effort, human and material resources since the cost of time does not takes more than minutes using the statistical programs by computers that make the application of statistical analysis procedures which is very simple and without complexity.